Intention to make preconception lifestyle changes among married men in an urban primary care clinic and its association with self-efficacy - Siti Solehah Ahmad Mazlan; Irmi Zarina Ismail; Navin Kumar Devaraj (Journal of Men's Health)
Men’s lifestyle is a relevant factor influencing pregnancy outcomes; however, their participation in preconception health is often overlooked. Therefore, the objective of this study is to determine the prevalence of men’s intention to implement preconception lifestyle changes and the factors that influence it. This single-centre, cross-sectional study used systematic random sampling to invite 352 married men with pregnancy plans who attended the clinic from February until April 2023. The respondent’s intention, self-efficacy, and social influences regarding preconception lifestyle changes were assessed through a validated self-administered questionnaire. A median score of 5 (minimum = 0, maximum = 10) was used as the cutoff to categorise intention as either low or high as the outcome variable. A total of 352 respondents were invited, and 284 (79.6%) men completed the questionnaire. Overall, 56.7% (n = 161) of married men indicated high intentions to make preconception lifestyle changes. The positive predictors of the intention to make preconception lifestyle changes among married men were having attended preconception counselling (adjusted odds ratio (aOR) = 13.33, 95% confidence interval (CI) = 2.82–63.02, p = 0.001), having higher self-efficacy (aOR = 1.76, 95% CI = 1.39–2.24, p < 0.001), influence of social norms (aOR = 1.39, 95% CI = 1.03–1.87, p = 0.030), and social influence from recognising the importance of other’s opinions (aOR = 1.23, 95% CI = 1.12–1.35, p < 0.001). More than half of the respondents have the intention to make preconception lifestyle changes. Preconception lifestyle interventions should focus on fostering self-efficacy among men with substance dependence to facilitate behavioural changes by leveraging their social influences.